Inkjet ink, method for forming cured product, and cured product
By using hydrophobizing silica particles and (meth)acrylate with aromatic rings in active energy line curing inkjet ink, the problem of difficult redispersion of the settled inorganic pigment is solved, and the stability and durability of the inkjet ink are improved.
Patent Information
- Application Number
- CN202411312317.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-26
- Filing Date
- 2024-09-20
- Publication Date
- 2025-03-28
AI Technical Summary
In the active energy line curable inkjet ink containing a polymerizable compound, the settled inorganic pigment is difficult to redisperse, resulting in a decrease in stability and durability of the inkjet ink.
The silica particles that are hydrophobized with hydrophobization have an average particle size smaller than the median diameter of the inorganic particles and a content smaller than the content of the inorganic particles. In the inkjet ink formed, the silica particles can be effectively adsorbed on the surface of the inorganic particles to inhibit their aggregation and settlement.
The redispersion of the settled inorganic pigment is significantly improved, the circulation and discharge properties of inkjet ink are stabilized, the durability of components such as inkjet heads is extended, and the ink injection bending and viscosity changes are avoided.
Smart Images

Figure BDA0005051013890000261 
Figure BDA0005051013890000271 
Figure BDA0005051013890000272
Abstract
Description
Technical Field
[0001] The present invention relates to an inkjet ink, a method for forming a cured product, and the cured product. Background Art
[0002] Inkjet inks containing inorganic particles such as titanium oxide as a white pigment and conductive particles are known. Inorganic particles tend to settle in the ink during storage or in standby before discharge, and have a problem of being difficult to redisperse after settling.
[0003] In order to solve this problem, in an inkjet recording ink composition described in Japanese Patent Application Laid-Open No. 2013-181055, silica particles having silanol groups on the surface are used together with an inorganic pigment in an aqueous ink containing water and an organic solvent as a solvent.
[0004] Similarly, in the active energy ray-curable inkjet ink described in Japanese Patent Application Laid-Open No. 2019-157062 containing silica particles, silica particles whose surfaces are modified with a (meth)acrylate compound are used in order to suppress sedimentation caused by aggregation of silica particles.
[0005] In Japanese Patent Publication No. 2013-181055, it is recorded that the use of silica particles can make the precipitated inorganic pigments easily redispersed. However, according to the knowledge of the inventors, in an active energy line-cured inkjet ink containing a polymerizable compound, even if the same silica particles as those in Japanese Patent Publication No. 2013-181055 are used, the precipitated inorganic pigments cannot become easily redispersed. In addition, even if the silica particles whose surfaces are modified with (meth) acrylate compounds recorded in Japanese Patent Publication No. 2019-157062 are used, the precipitated inorganic pigments in the active energy line-cured inkjet ink cannot become easily redispersed.
[0006] In addition, according to another understanding of the inventors, the active energy ray-cured inkjet ink to which the same silica particles as those in Japanese Patent Publication No. 2013-181055 and Japanese Patent Publication No. 2019-157062 are added is prone to bending of the ejection from the inkjet head. In addition, the durability of components such as the inkjet head and the flow path is easily reduced. Summary of the invention
[0007] One aspect of the present invention for solving the above-mentioned problems relates to active energy ray-curable inkjet inks of the following [1] to
[10] .
[0008] [1] An active energy ray-curable inkjet ink comprising a polymerizable compound, inorganic particles, and silica particles, wherein the silica particles are hydrophobicized and do not have a polymerizable group, the average particle size of the silica particles is smaller than the median diameter of the inorganic particles, and the mass-based content of the silica particles is less than the mass-based content of the inorganic particles.
[0009] [2] The inkjet ink according to [1], wherein the polymerizable compound contains a (meth)acrylate.
[0010] [3] The inkjet ink according to [2], wherein the (meth)acrylate contains a monofunctional polymerizable compound having an aromatic ring.
[0011] [4] The inkjet ink according to any one of [1] to [3], which contains substantially no water and substantially no organic solvent.
[0012] [5] The inkjet ink according to any one of [1] to [4], wherein the average particle diameter of the silica particles is 1 / 20 or less of the median diameter of the inorganic particles.
[0013] [6] The inkjet ink according to any one of [1] to [5], wherein the content of the silica particles is 0.01% by mass or more and 5% by mass or less relative to the total mass of the inkjet ink.
[0014] [7] The inkjet ink according to any one of [1] to [6], wherein the average particle size of the inorganic particles is 0.5 μm or more and 5 μm or less.
[0015] [8] The inkjet ink according to any one of [1] to [7], wherein the inorganic particles have a D 50 / D 90 It is 0.1 or more and 0.9 or less.
[0016] [9] The inkjet ink according to any one of [1] to [8], wherein the inorganic particles are light-storing pigments.
[0017]
[10] The inkjet ink according to any one of [1] to [9], comprising a thermal curing agent.
[0018] Another aspect of the present invention for solving the above-mentioned problems relates to a method for forming a cured product according to the following
[11] to
[12] .
[0019]
[11] A method for forming a cured product, comprising: applying the inkjet ink according to any one of [1] to
[10] to a substrate; and irradiating the applied inkjet ink with active energy rays.
[0020]
[12] The method for forming a cured product according to
[11] , wherein the step of applying the ink to the substrate is performed while circulating the inkjet ink.
[0021] Another aspect of the present invention for solving the above-mentioned problems relates to the cured product of the following
[13] .
[0022]
[13] A cured product formed using the inkjet ink according to any one of [1] to
[10] . DETAILED DESCRIPTION
[0023] Hereinafter, one or more embodiments of the present invention will be described with reference to the drawings. However, the scope of the present invention is not limited to the disclosed embodiments.
[0024] 1. Inkjet ink
[0025] One embodiment of the present invention relates to an active energy ray-curable inkjet ink (hereinafter, also simply referred to as “ink”). The ink contains a polymerizable compound, inorganic particles, and hydrophobicized silica particles.
[0026] In the ink involved in this embodiment, it is believed that particles smaller than the inorganic pigment, i.e., silica particles, are adsorbed on the surface of the inorganic pigment. As for the silica particles, the filling of the settled inorganic particles and the aggregation between the inorganic particles are suppressed by adsorption on the surface of the inorganic pigment. Therefore, it is believed that the silica particles easily redisperse the settled inorganic particles.
[0027] The ink related to the present embodiment is an active energy ray-curable ink containing a polymerizable compound. Moreover, the hydrophobized silica particles contained in the above-mentioned ink are easily wetted by the polymerizable compound as a liquid component. Therefore, in the ink related to the present embodiment, the silica particles are well dispersed. The well-dispersed silica is well adsorbed on the inorganic particles, so it is believed that the ink related to the present embodiment makes it easy to redisperse the precipitated inorganic particles. It should be noted that the silica particles described in Patent Document 1 are hydrophilized. For such silica particles, the wettability to polymerizable compounds is not good. Therefore, it is believed that the silica particles described in Patent Document 1 are difficult to adsorb on inorganic particles and it is difficult to improve the redispersibility of the precipitated inorganic particles.
[0028] In addition, the ink related to the present embodiment contains silica particles without polymerizable groups. As for the silica particles whose surfaces are modified by (meth)acrylate compounds as described in Patent Document 2, the (meth)acryloyl groups on the surface undergo polymerization reaction during the storage of the ink, during the flow, when the ink is heated inside the inkjet head, etc. Moreover, as for the above-mentioned silica particles, through the polymerization reaction, the silica particles condense and are easily separated from the surface of the inorganic particles. Therefore, it is believed that the above-mentioned silica particles are difficult to improve the redispersibility of the precipitated inorganic particles.
[0029] It should be noted that if the settled inorganic particles cannot be redispersed, the concentration of the inorganic particles in the discharged inkjet ink is likely to change, or the viscosity of the inkjet ink changes and the discharge becomes unstable. In addition, when the inkjet ink before discharge is circulated in the ink flow path and the inkjet head, the circulation of the inkjet ink is difficult to stabilize. In this embodiment, the inorganic particles that settle the silica particles are easily redispersed, and these problems are unlikely to occur.
[0030] In addition, inorganic particles are usually high in hardness. Moreover, in terms of the high hardness inorganic particles condensed in the ink, sometimes contact with the components of the inkjet head or the ink flow path and deteriorate these components. Furthermore, the condensed inorganic particles sometimes stick to the nozzle surface and peel off the water-repellent film on the discharge surface of the nozzle plate, or grind the nozzle opening to deform it, resulting in ink ejection bending and poor ejection. In contrast, in the present embodiment, the silica particles well wetted by the polymerizable compound are well adsorbed on the inorganic particles, inhibiting the aggregation of the inorganic particles. In addition, in terms of the silica particles used in the present embodiment, when the ink is stored, heated inside the inkjet head during flow, etc., it is also difficult to detach from the surface of the inorganic pigment, and it is difficult to cause the aggregation of inorganic particles. Therefore, the ink related to the present embodiment is difficult to reduce the durability of components such as the inkjet head and the ejection of the ink.
[0031] Hereinafter, each component will be described.
[0032] 1-1. Polymerizable compounds
[0033] The polymerizable compound is a compound that polymerizes and crosslinks by irradiation with active energy rays.
[0034] The polymerizable compound may be a monomer, an oligomer, a polymer, or a mixture thereof.
[0035] The polymerizable compound may be a monofunctional compound or a polyfunctional compound. When the cured product is to be made soft, it is preferred to include a monofunctional compound, and when the hardness of the cured product is to be increased, it is preferred to include a polyfunctional compound. In addition, from the viewpoint of achieving these balances, the polymerizable compound may include both a monofunctional compound and a polyfunctional compound.
[0036] The polymerizable compound may be a radical polymerizable compound or a cation polymerizable compound. In addition, the polymerizable compound may be used in combination with a radical polymerizable compound and a cation polymerizable compound.
[0037] The radical polymerizable compound is a compound having an ethylenically unsaturated bond which can be radical polymerized.
[0038] Examples of compounds having free radical polymerizable ethylenically unsaturated bonds include unsaturated carboxylic acids and salts thereof, unsaturated carboxylic acid ester compounds, unsaturated carboxylic acid carbamate compounds, unsaturated carboxylic acid amide compounds and anhydrides thereof. Examples include acrylonitrile, styrene, unsaturated polyesters, unsaturated polyethers, unsaturated polyamides, and unsaturated carbamates. Examples of unsaturated carboxylic acids include (meth) acrylic acid, itaconic acid, crotonic acid, isocrotonic acid, and maleic acid.
[0039] Among them, the free radical polymerizable compound is preferably an unsaturated carboxylic acid ester compound, more preferably a (meth) acrylate. As for (meth) acrylate, due to its own high thermal stability, it can also improve the thermal stability of the ink. Therefore, the ink containing (meth) acrylate has high thermal stability inside the inkjet head and is less likely to bend during ejection. (Meth) acrylate can be a monomer described later, or an oligomer, a mixture of a monomer and an oligomer, a modified product, an oligomer having a polymerizable functional group, etc.
[0040] In addition, in this specification, (meth)acrylate means acrylate or methacrylate, (meth)acryloyl means acryloyl or methacryloyl, and (meth)acrylic acid means acrylic acid or methacrylic acid.
[0041] Examples of monofunctional (meth)acrylates include isoamyl (meth)acrylate, stearyl (meth)acrylate, lauryl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, isomyristyl (meth)acrylate, and isostearyl (meth)acrylate. Examples include 2-phenoxyethyl (meth)acrylate, 2-ethylhexyl-diglycol (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 2-(meth)acryloyloxyethyl hexahydrophthalic acid. Examples include butoxyethyl (meth)acrylate, ethoxydiglycol (meth)acrylate, and methoxydiglycol (meth)acrylate. Examples include methoxypolyethylene glycol (meth)acrylate, methoxypropylene glycol (meth)acrylate, and o-phenylphenoxyethyl (meth)acrylate. Examples include benzyl (meth)acrylate, phenol (meth)acrylate, m-phenoxybenzyl (meth)acrylate, and cyclic trimethylolpropane formal (meth)acrylate. Contains ethoxylated phenoxy (meth) acrylate, alkoxylated phenol (meth) acrylate, tetrahydrofurfuryl (meth) acrylate, isobornyl (meth) acrylate. Contains 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 2-hydroxy-3-phenoxypropyl (meth) acrylate, 2-hydroxy-o-phenylphenol propyl (meth) acrylate. Contains 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl-2-hydroxyethyl-phthalic acid and tert-butylcyclohexyl (meth) acrylate, etc.
[0042] Examples of multifunctional (meth)acrylates include triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, and polyethylene glycol di(meth)acrylate. Dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate are included. 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and 1,9-nonanediol di(meth)acrylate are included. Neopentyl glycol di(meth)acrylate, tricyclodecane dimethanol diacrylate, and dihydroxymethyl-tricyclodecane di(meth)acrylate are included. Bisphenol A type di(meth)acrylate and hydroxypivalic acid neopentyl glycol di(meth)acrylate are included. Bifunctional (meth)acrylates including polytetramethylene glycol di(meth)acrylate, polyethylene glycol diacrylate, dipropylene glycol diacrylate, and tripropylene glycol diacrylate are included. Contains trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate. Contains dipentaerythritol hexa(meth)acrylate, di(trimethylolpropane) tetra(meth)acrylate. Contains trifunctional or higher (meth)acrylates including glycerol propoxy tri(meth)acrylate and pentaerythritol ethoxy tetra(meth)acrylate.
[0043] The (meth)acrylate may be a modified product. Examples of the (meth)acrylate as a modified product include ethylene oxide-modified trimethylolpropane tri(meth)acrylate and ethylene oxide-modified pentaerythritol tetraacrylate. Caprolactone-modified (meth)acrylate includes caprolactone-modified trimethylolpropane tri(meth)acrylate. Caprolactam-modified (meth)acrylate includes caprolactam-modified dipentaerythritol hexa(meth)acrylate.
[0044] The (meth)acrylate may be a polymerizable oligomer. Examples of the (meth)acrylate as a polymerizable oligomer include epoxy (meth)acrylate oligomers, aliphatic urethane (meth)acrylate oligomers, aromatic urethane (meth)acrylate oligomers, polyester (meth)acrylate oligomers, and linear (meth)acrylic oligomers.
[0045] Examples of the cationically polymerizable compound include epoxy compounds, vinyl ether compounds, and oxetane compounds.
[0046] Examples of epoxy compounds include 3,4-epoxycyclohexylmethyl-3′,4′-epoxycyclohexanecarboxylate, bis(3,4-epoxycyclohexylmethyl)adipate, and vinylcyclohexene monoepoxide. Examples include ε-caprolactone-modified 3,4-epoxycyclohexylmethyl-3′,4′-epoxycyclohexanecarboxylate and 1-methyl-4-(2-methyloxiranyl)-7-oxabicyclo[4,1,0]heptane. Examples include alicyclic epoxy resins such as 2-(3,4-epoxycyclohexyl-5,5-spiro-3,4-epoxy)cyclohexanone-m-dioxane and bis(2,3-epoxycyclopentyl)ether. Examples include diglycidyl ether of neopentyl glycol, diglycidyl ether of 1,4-butanediol, diglycidyl ether of 1,6-hexanediol, and triglycidyl ether of glycerol. Contains triglycidyl ether of trimethylolpropane, diglycidyl ether of ethylene glycol, and diglycidyl ether of diethylene glycol. Contains diglycidyl ether of triethylene glycol, diglycidyl ether of propylene glycol, and diglycidyl ether of polyethylene glycol. Contains diglycidyl ether of propylene glycol. Contains aliphatic epoxy compounds such as polyglycidyl ethers of polyether polyols obtained by adding aliphatic polyols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, and glycerol to one or more oxyalkylenes (ethylene oxide and propylene oxide, etc.). Contains di- or polyglycidyl ethers of bisphenol A or its oxyalkylene adducts, di- or polyglycidyl ethers of hydrogenated bisphenol A or its oxyalkylene adducts, and aromatic epoxy compounds such as novolac epoxy resins.
[0047] Examples of vinyl ether compounds include ethyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, octadecyl vinyl ether, cyclohexyl vinyl ether, hydroxybutyl vinyl ether, and 2-ethylhexyl vinyl ether. Examples include cyclohexanedimethanol monovinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, and isopropenyl ether-o-propylene carbonate. Examples include monovinyl ether compounds including dodecyl vinyl ether, diethylene glycol monovinyl ether, and octadecyl vinyl ether. Examples include ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, propylene glycol divinyl ether, and dipropylene glycol divinyl ether. Examples include di- or tri-vinyl ether compounds including butanediol divinyl ether, hexanediol divinyl ether, cyclohexanedimethanol divinyl ether, and trimethylolpropane trivinyl ether.
[0048] In the example of oxetane compound, 3-hydroxymethyl-3-methyloxetane, 3-hydroxymethyl-3-ethyloxetane, 3-hydroxymethyl-3-propyloxetane, 3-hydroxymethyl-3-n-butyloxetane are included. 3-hydroxymethyl-3-phenyloxetane, 3-hydroxymethyl-3-benzyloxetane, 3-hydroxyethyl-3-methyloxetane, 3-hydroxyethyl-3-ethyloxetane are included. 3-hydroxyethyl-3-propyloxetane, 3-hydroxyethyl-3-phenyloxetane, 3-hydroxypropyl-3-methyloxetane, 3-hydroxypropyl-3-ethyloxetane are included. Contains 3-hydroxypropyl-3-propyloxetane, 3-hydroxypropyl-3-phenyloxetane, 3-hydroxybutyl-3-methyloxetane, 3,3'-(oxybismethylene)bis(3-ethyloxetane). Contains 1,4-bis{[(3-ethyl-3-oxetane)methoxy]methyl}benzene, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane and di[1-ethyl(3-oxetane)]methyl ether.
[0049] The polymerizable compound preferably contains a compound having an aromatic ring in the molecule. The aromatic ring is structurally stable and therefore difficult to abstract hydrogen. Therefore, in the case of a polymerizable compound having an aromatic ring in the molecule, yellowing of the solidified material due to a hydrogen abstraction reaction caused by a large number of free radicals generated during the solidification of the ink is unlikely to occur. In addition, the compound having an aromatic ring in the molecule is preferably a monofunctional polymerizable compound. In the case of a polymerizable compound having an aromatic ring at the end, since the wettability to inorganic particles is high, it is easy to redisperse the precipitated inorganic particles.
[0050] The content of the polymerizable compound having an aromatic ring is preferably 10% by mass or more and 80% by mass or less, and more preferably 20% by mass or more and 70% by mass or less, based on the total mass of the ink.
[0051] Examples of polymerizable compounds having an aromatic ring include phenol 4EO modified (meth)acrylate, 2-phenoxyethyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, benzyl (meth)acrylate, and phenol (meth)acrylate. Examples include m-phenoxybenzyl (meth)acrylate, alkoxylated phenol (meth)acrylate, 2-hydroxy-o-phenylphenol propyl (meth)acrylate, and EO modified o-phenylphenol (meth)acrylate. Examples include bisphenol fluorene di(meth)acrylate (A-BPEF), bisphenol A type 10EO modified di(meth)acrylate, bisphenol A type di(meth)acrylate, bisphenol A type PO modified di(meth)acrylate, and bisphenol A type EO modified di(meth)acrylate. Examples include 2-hydroxy-3-phenoxypropyl (meth)acrylate, and the like. Among these, preferred are phenol 4EO-modified (meth)acrylate, 2-phenoxyethyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, benzyl (meth)acrylate, phenol (meth)acrylate, m-phenoxybenzyl (meth)acrylate, alkoxylated phenol (meth)acrylate, 2-hydroxy-o-phenylphenol propyl (meth)acrylate, EO-modified o-phenylphenol (meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate.
[0052] The content of the polymerizable compound is preferably 30% by mass or more and 97% by mass or less, and more preferably 60% by mass or more and 95% by mass or less, relative to the total mass of the ink. The content of the monofunctional polymerizable compound having an aromatic ring is preferably 10% by mass or more and 60% by mass or less, and more preferably 20% by mass or more and 50% by mass or less, relative to the total mass of the ink.
[0053] 1-2. Inorganic particles
[0054] The inorganic particles are not particularly limited in type. The inorganic particles may be pigment particles that impart characteristics such as color tone, conductivity, insulation, heat dissipation, and negative thermal expansion coefficient to the cured product formed using the ink, or particles that are added separately from the pigment to adjust the physical properties of the cured product.
[0055] The inorganic particles may be particles containing atoms other than carbon as a main component. The term "containing as a main component" means that 50% by mass or more of the total mass of the inorganic particles are atoms other than carbon.
[0056] Examples of inorganic particles include
[0057] Silica particles,
[0058] Metal oxide particles such as titanium oxide particles, aluminum oxide particles, zirconium oxide particles, zinc oxide particles, and iron oxide particles
[0059] Metal hydroxide particles such as magnesium hydroxide particles, aluminum hydroxide particles, and porous calcium hydroxide particles Nitride particles such as silicon nitride particles, titanium nitride particles, and aluminum nitride particles
[0060] Bright pigment particles such as silver particles (or conductive particles),
[0061] Glass particles such as glass beads and glass flakes,
[0062] Silicate particles such as magnesium silicate particles,
[0063] Kaolin particles, calcined kaolin particles, ceramic particles such as clay, talc, and zeolite, particles obtained by combining multiple materials such as pearlescent pigment particles, and
[0064] Light-storing pigment particles, etc., which can absorb light of a predetermined wavelength to store light energy and emit the light for a long period of time as light of a wavelength different from that of light having absorbed the stored light energy.
[0065] Examples of the luminescent pigment include those obtained by activating a mother crystal as a metal compound.
[0066] The above-mentioned examples of the mother crystal include sulfides such as zinc sulfide, calcium sulfide, germanium sulfide, strontium sulfide, and yttrium sulfide. Metal oxides such as calcium oxide, strontium oxide, barium oxide, aluminum oxide, and cerium oxide. Aluminates such as calcium aluminate, strontium aluminate, and barium aluminate are included. Among these, strontium aluminate (SrAl2O4:Eu, Dy) is preferred.
[0067] Examples of the activator for activating the mother crystal include europium, terbium, yttrium, zirconium, dysprosium, and barium, etc. Among these, europium and dysprosium are preferred.
[0068] The peak wavelength of the excitation spectrum of the luminescent pigment is preferably 300 nm to 400 nm. If the peak wavelength of the excitation spectrum of the luminescent pigment is within the above range, the luminescent pigment can be sufficiently excited by sunlight, and the cured product can be easily used outdoors.
[0069] The peak wavelength of the light emission spectrum of the light-storing pigment can be, for example, 400 nm to 700 nm, and is preferably 450 nm to 600 nm from the viewpoint of further improving the visibility of the cured product.
[0070] Among these inorganic particles, bright pigment particles, zinc oxide particles, and luminescent pigment particles are preferred. Furthermore, since silica particles are easily adsorbed and redispersibility after sedimentation is easily improved, zinc oxide particles, pearlescent pigment particles, and luminescent pigment particles are more preferred, and luminescent pigment particles are even more preferred.
[0071] The shape of the inorganic particles is not particularly limited, and may be spherical, or may be non-spherical such as a flat plate or a whisker. Among these, a spherical shape is preferred from the perspective of the effect of improving the redispersibility after the sedimentation caused by the silica particles. For example, the inorganic particles preferably have a ratio of major diameter to minor diameter, i.e., an aspect ratio of 1.0 to 1.5, more preferably 1.0 to 1.2.
[0072] The major diameter and minor diameter of the inorganic particles are obtained from the inorganic particles in the ink depicted in an image taken by a transmission electron microscope (TEM), a scanning electron microscope (SEM), etc. The major diameter and minor diameter of 1,000 inorganic particles arbitrarily selected from the image can be averaged.
[0073] The median diameter of the inorganic particles in the ink is not particularly limited, and can be set to be 0.2 μm or more and 20 μm or less, preferably 0.3 μm or more and 10 μm or less, more preferably 0.5 μm or more and 5 μm or less, and further preferably 1.0 μm or more and 5 μm or less. The larger the median diameter, the easier it is to increase the adsorption amount of silica particles for inorganic particles, and the easier it is to improve the redispersibility after sedimentation by silica particles. In addition, the larger the median diameter, the more difficult it is to fill the precipitated inorganic particles, and the easier it is to redisperse. The smaller the median diameter, the better the discharge from the inkjet head, and even if condensed, it is difficult to damage components such as the inkjet head.
[0074] The median diameter of the inorganic particles can be determined by using the particle size at which the cumulative value of the volume-based particle size distribution is 50% (D 50 ).
[0075] The particle size (D) at which the cumulative value of the volume-based particle size distribution of the inorganic particles in the ink becomes 90% 90 ), it can be set to be 1.0 μm or more and 20 μm or less, preferably 1.5 μm or more and 10 μm or less, and more preferably 2.0 μm or more and 8 μm or less. It is easy to increase the amount of silica particles adsorbed on inorganic particles, and it is easy to use silica particles to improve the redispersibility after sedimentation. In addition, D 90 The larger the value, the more difficult it is to fill the settled inorganic particles and the easier it is to redisperse them. 90 The smaller the particle size, the better the discharge performance from the inkjet head becomes, and even if the particles aggregate, the inkjet head and other components are less likely to be damaged.
[0076] In addition, the inorganic particles are preferably D 50 / D 90 It is 0.2 or more and 0.8 or less, and more preferably 0.3 or more and 0.6 or less. 50 / D 90As the particle size is smaller, the particle size distribution can be broadened, and a cured product densely filled with inorganic particles can be formed, and the weather resistance of the cured product can be improved.
[0077] In order to explain, D 50 and D 90 For example, it can be set as a value measured using a particle size measuring device such as LUMiSizer or LUM Japan Co., Ltd.
[0078] The specific gravity of the inorganic particles can be set to be 2 to 6, preferably 2.5 to 5, and more preferably 3 to 4.5. The greater the specific gravity, the easier it is for the inorganic particles in the ink to settle, and the effect of improving the redispersibility after the sedimentation by the silica particles is more significantly manifested.
[0079] The inorganic particles may be dispersed using a dispersant. The inorganic particles may be dispersed using only one dispersant or using two or more dispersants.
[0080] In the example of dispersant, carboxylic acid esters with hydroxyl groups, salts of long-chain polyaminoamide and high molecular weight acid esters, salts of high molecular weight polycarboxylic acids, salts of long-chain polyaminoamide and polar acid esters are included. High molecular weight unsaturated acid esters, polymer copolymers, modified polyurethanes, modified polyacrylates, polyether ester type anionic active agents are included. Naphthalenesulfonic acid formalin condensate salts, aromatic sulfonic acid formalin condensate salts, polyoxyethylene alkyl phosphates are included. Polyoxyethylene nonylphenyl ether and stearylamine acetate are included. In the example of commercially available products of pigment dispersants, Solsperse series (made by Avecia, "Solsperse" is a registered trademark of the company), PB series (made by Ajinomoto Ficinno Co., Ltd.), EFKA series (made by BASF, "EFKA" is a registered trademark of the company), etc. are included.
[0081] The content of the dispersant is preferably 0.01% by mass or more and 20% by mass or less relative to the total mass of the inorganic particles.
[0082] The content of the inorganic particles can be set according to the purpose of the inorganic particles. For example, the content of the inorganic particles can be set to 1% by mass or more and 60% by mass or less, preferably 2% by mass or more and 50% by mass or less, and more preferably 3% by mass or more and 30% by mass or less, relative to the total mass of the ink. The less the content of the inorganic particles, the more the redispersibility of the precipitated inorganic particles is improved.
[0083] 1-3. Silica particles
[0084] Silica particles are particles whose average particle diameter is smaller than the median diameter of inorganic particles. Silica particles smaller than inorganic particles are easily adsorbed on the surface of inorganic particles, and are easy to suppress the filling and agglomeration of inorganic particles. It is also believed that: thus, silica particles easily redisperse the settled inorganic particles. In addition, for the same reason, it is believed that silica particles suppress the reduction of the durability of components such as inkjet heads when using ink containing inorganic pigments, the ejection of ink, etc.
[0085] Silica particles may be particles composed of silica (SiO2), and may be particles containing silica and other substances as the main component. In addition, silica particles may be core-shell particles comprising a core and a shell containing silica. It should be noted that as the main component, it is included or included... as the main component means that more than 50% by mass of the total mass of the particles is silica. From the viewpoint of improving the redispersibility and cyclic stability of the precipitated inorganic particles, it is preferred that the silica particles are particles consisting only of silica. Silica particles may be natural or synthetic, and synthetics are preferred from the perspective of easily adjusting the average particle size and particle size distribution.
[0086] The silica particles as the composite can be silica particles manufactured by a dry method or by a wet method. In the example of silica particles manufactured by a dry method, combustion silica particles manufactured by a combustion method and deflagration silica particles manufactured by a deflagration method are included. In the example of silica particles manufactured by a wet method, sedimentation silica particles manufactured by a sedimentation method, silica gel manufactured by a gel method, colloidal silica, and sol-gel silica are included. Among these, combustion silica, deflagration silica, and sol-gel silica are preferred, and sol-gel silica is more preferred, from the perspective of high adsorption of inorganic particles.
[0087] The silicon dioxide particles are hydrophobized. The silicon dioxide particles treated by hydrophobization are easily wetted by polymerizable compounds and are easily well dispersed in ink. Therefore, the silicon dioxide particles treated by hydrophobization are easily adsorbed on the surface of inorganic particles in ink, which easily improves the redispersibility of the precipitated inorganic particles, or suppresses the reduction of the durability, ejection, etc. of the component.
[0088] The method for hydrophobic treatment is not particularly limited, and the silane coupling agent with hydrophobic group (alkyl group etc.), the titanium coupling agent with hydrophobic group (alkyl group etc.), polysiloxane, disilazane, silicone oil and long-chain fatty acid etc. can be used for the treatment. In the example of the compound for hydrophobic treatment, the chlorosilanes including methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, phenyltrichlorosilane, diphenyldichlorosilane, tert-butyldimethylchlorosilane and vinyltrichlorosilane etc. are included. Tetramethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, o-methylphenyltrimethoxysilane are included. P-methylphenyltrimethoxysilane, n-butyltrimethoxysilane, isobutyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane are included. Contains dodecyltrimethoxysilane, tetraethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, diphenyldiethoxysilane, isobutyltriethoxysilane. Contains decyltriethoxysilane, vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldimethoxysilane. Contains γ-mercaptopropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane. Contains alkoxysilanes including γ-(2-aminoethyl)aminopropyltrimethoxysilane and γ-(2-aminoethyl)aminopropylmethyldimethoxysilane. Contains polysiloxanes including hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, hexamethyldisiloxane, octamethyltrisiloxane, etc. Contains hexamethyldisilazane, hexaethyldisilazane, hexapropyldisilazane, hexabutyldisilazane, hexapentyldisilazane, hexahexyldisilazane, hexacyclohexyldisilazane. Contains disilazanes including hexaphenyldisilazane, divinyltetramethyldisilazane, and dimethyltetravinyldisilazane. Contains dimethyl silicone oil, methyl hydrogen silicone oil, methylphenyl silicone oil, alkyl modified silicone oil, chloroalkyl modified silicone oil, chlorophenyl modified silicone oil. Contains silicone oils including fatty acid modified silicone oil, polyether modified silicone oil, alkoxy modified silicone oil, methanol modified silicone oil, amino modified silicone oil, fluorine modified silicone oil, and terminal reactive silicone oil. Contains long-chain fatty acids or their salts such as undecanoic acid, lauric acid, tridecanoic acid, dodecanoic acid, myristic acid, palmitic acid, pentadecanoic acid, stearic acid, heptadecanoic acid, arachidic acid, montanic acid, oleic acid, linoleic acid, and arachidonic acid.
[0089] It is explained that in this specification, in the above-mentioned hydrophobic treatment, the treatment comprising a polymerizable group is not included. In the example of a polymerizable group, epoxy, (meth) acryloyl, and vinyl etc. are included. Since hydroxyl and silanol groups do not react with polymerizable compounds, they are not included in the polymerizable group.
[0090] The hydrophobization degree of the hydrophobized silica particles is preferably 30% or more and 80% or less, and more preferably 50% or more and 75% or less.
[0091] The hydrophobization degree of the silica particles is measured by adding 0.2% by mass of silica particles to 50 ml of ion exchange water, and dropping methanol from a dropper while stirring with a magnetic stirrer to obtain the methanol mass fraction in the methanol-water mixed solution at the end point where all the silica particles sink.
[0092] The average particle size of the silica particles is preferably less than 1 / 2 of the median diameter of the inorganic particles, more preferably less than 1 / 10, further preferably less than 1 / 20, and particularly preferably less than 1 / 50. The smaller the ratio of the average particle size of the silica particles relative to the median diameter of the inorganic particles, the easier it is to make the silica particles adsorbed on the surface of the inorganic particles. In particular, by making the average particle size of the silica particles less than 1 / 20 of the median diameter of the inorganic particles, the ratio of the specific surface area of the silica particles relative to the surface area of the inorganic particles can be made larger, and the silica particles can be more easily adsorbed on the surface of the inorganic particles. The lower limit of the ratio of the average particle size of the silica particles relative to the median diameter of the inorganic particles is not particularly limited, and is preferably more than 1 / 500.
[0093] The average particle size of the silica particles is preferably 0.005 μm or more and 1.5 μm or less, more preferably 0.01 μm or more and 1.0 μm or less, and further preferably 0.05 μm or more and 0.5 μm or less. The smaller the average particle size of the silica particles, the more the redispersibility of the precipitated inorganic particles is improved. If the average particle size of the silica particles is increased to some extent, the specific surface area of the inorganic particles to which the silica particles are attached can be reduced, and it is difficult to cause damage to the nozzle surface caused by the inorganic particles.
[0094] The average particle size of the silica particles can be set to the manufacturer's published value. In addition, it is also possible to use a particle size measuring device and a dynamic light scattering method to measure as a volume average diameter. For example, the slurry containing silica particles is diluted with ion exchange water so that the content of the silica particles becomes 0.1% by mass, and the diluted slurry is irradiated with a laser, and the intensity of scattered light scattered from the silica inorganic particles is measured in microseconds. The detected scattering intensity distribution caused by the silica particles is substituted into the normal distribution, and the Z average particle size of the silica particles is obtained by the cumulative analysis method. As a particle size measuring device, for example, the Zetasizer ZS manufactured by Spectoris can be used. In the particle size measuring device, a data analysis software is provided, and the measurement data is automatically analyzed by the data analysis software, and the Z average particle size can be calculated.
[0095] The shape of the silica particles is preferably spherical. For example, the silica particles preferably have a ratio of major diameter to minor diameter, i.e., an aspect ratio of 1.0 to 1.5, more preferably 1.0 to 1.2. The major diameter and minor diameter of the silica particles can be measured in the same manner as the major diameter and minor diameter of the above-mentioned inorganic particles.
[0096] The content of silica particles relative to the total mass of ink can be set to 0.01 mass % or more and 5 mass % or less, preferably 0.01 mass % or more and 3 mass % or less, more preferably 0.01 mass % or more and 2 mass % or less, and further preferably 0.01 mass % or more and 1.5 mass % or less. If the content of silica particles is 0.01 mass % or more, the redispersibility of the precipitated inorganic particles is improved. If the content of silica particles is 5 mass % or less, the reduction of ejectability caused by the silica particles not adsorbed on the inorganic particles, the damage of components such as inkjet heads, etc. are suppressed.
[0097] The ratio of the content of silica particles to the content of inorganic particles (content of silica particles (by mass) / content of inorganic particles (by mass)) is preferably 0.0004 to 0.3, more preferably 0.004 to 0.2, and further preferably 0.01 to 0.1.
[0098] 1-3. Other ingredients
[0099] The ink may further contain other ingredients such as a photopolymerization initiator, an organic pigment, a dye, a thermal curing agent, a surfactant, a fluorescent brightener, a gelling agent, and a polymerization inhibitor.
[0100] The photopolymerization initiator can be a radical initiator when the ink contains a radical polymerizable compound, or a cationic initiator (photoacid generator) when the ink contains a cation polymerizable compound. When polymerization is initiated by irradiation with electron beams, the ink may not contain a photopolymerization initiator.
[0101] Examples of the radical polymerization initiator include hydrogen abstraction type photopolymerization initiators and intramolecular cleavage type photopolymerization initiators. The hydrogen abstraction type photopolymerization initiators include intramolecular hydrogen abstraction type photopolymerization initiators and intermolecular hydrogen abstraction type photopolymerization initiators.
[0102] The intramolecular hydrogen abstraction type photopolymerization initiator is a photopolymerization initiator that is excited by the irradiation of active energy lines, generates a hydrogen abstraction reaction in the molecule, and generates free radicals. In the example of the intramolecular hydrogen abstraction type photopolymerization initiator, methyl benzoylformate-based photopolymerization initiators such as methyl phenylglyoxylate are included. Hydroxyphenyl-based photopolymerization initiators such as a mixture of hydroxyphenylacetic acid-2-[2-oxo-2-phenylacetoxy-ethoxy]ethyl and hydroxyphenylacetic acid 2-[2-hydroxy-ethoxy]ethyl are included. Among these, it is difficult to extract hydrogen from the molecular chain of the polymerizable compound in the polymerization, and preferably compounds with a glyoxylic acid structure such as methyl benzoylformate-based photopolymerization initiators.
[0103] Examples of commercially available products of the intramolecular hydrogen abstraction type photopolymerization initiator include Omnirad MBF and Omnirad 754 (both manufactured by IGM Res ins, and “Omnirad” is a registered trademark of the company).
[0104] The intermolecular hydrogen abstraction type photopolymerization initiator is a photopolymerization initiator that is excited by the irradiation of active energy rays such as ultraviolet rays, and extracts hydrogen from other molecules to generate free radicals. Examples of intermolecular hydrogen abstraction type photopolymerization initiators include benzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, and 4,4'-dichlorobenzophenone. Hydroxybenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, and acrylated benzophenone are included. Initiators of benzophenone systems including 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, and 3,3'-dimethyl-4-methoxybenzophenone are included. Thioxanthone systems such as 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, and 2,4-dichlorothioxanthone are included.
[0105] Examples of commercially available intermolecular hydrogen abstraction type photopolymerization initiators include Omnirad 500 (manufactured by IGM Resins) and Speedcure ITX (manufactured by Sartomer; “Speedcure” is a registered trademark of Alchema France).
[0106] Examples of intramolecular cleavage type photopolymerization initiators include 2-hydroxy-2-methyl-1-phenylpropane-1-one and benzyl dimethyl ketal. 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone and 1-hydroxycyclohexyl-phenylketone. Acetophenone-based initiators include 2-methyl-2-morpholino(4-methylthiophenyl)propane-1-one and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone. Benzoin-based initiators include benzoin, benzoin methyl ether, and benzoin isopropyl ether. Acylphosphine oxide-based initiators include 2,4,6-trimethylbenzoin diphenylphosphine oxide and bis(2,4,6-trimethylbenzoin)phenylphosphine oxide.
[0107] Examples of commercially available intramolecular cleavage-type photopolymerization initiators include Omnirad 127, Omnirad 184, Omnirad 651, Omnirad 2959, Omnirad 819, and Esacure One (all manufactured by IGM Res ins).
[0108] The content of the photopolymerization initiator is preferably 3% by mass or more and 20% by mass or less, more preferably 3% by mass or more and 15% by mass or less, further preferably 3% by mass or more and 10% by mass or less, and particularly preferably 5% by mass or more and 10% by mass or less, relative to the total mass of the polymerizable material. By making the above content 3% by mass or more, the curability and adhesion of the ink can be further improved.
[0109] Examples of organic pigments include red pigments, yellow pigments, cyan pigments, and white pigments for inks used for image formation. As for these pigments, known pigments can be used. Examples of dyes include red dyes, yellow dyes, cyan dyes, and the like for inks used for image formation. As for these dyes, known dyes can be used.
[0110] Examples of thermosetting agents include polyfunctional epoxy compounds, polyfunctional oxetane compounds, imidazoles, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, and 4-phenylimidazole. Examples include imidazole derivatives such as 1-cyanoethyl-2-phenylimidazole, 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole, dicyandiamide, benzyldimethylamine, and 4-(dimethylamino)-N,N-dimethylbenzylamine. Amine compounds such as 4-methoxy-N,N-dimethylbenzylamine and 4-methyl-N,N-dimethylbenzylamine. Examples include phosphine compounds such as tributylphosphine and triphenylphosphine, hydrazine compounds such as adipic acid dihydrazide and sebacic acid dihydrazide, melamine resins, benzoguanamine resins, melamine derivatives, and amino resins such as benzoguanamine derivatives. Examples include blocked isocyanate compounds, cyclic carbonate compounds, cyclic (thio)ether compounds, bismaleimide, and carbodiimide resins. Contains aromatic amines, reactants of amine compounds and epoxy compounds, as well as phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, hexahydrophthalic anhydride, and tetrahydrophthalic anhydride. Contains 3-chlorophthalic anhydride, 4-chlorophthalic anhydride, benzophenonetetracarboxylic anhydride, succinic anhydride, methylsuccinic anhydride, dimethylsuccinic anhydride, and dichlorosuccinic anhydride. Contains anhydrides such as nadic methyl acid, dodecylsuccinic acid, chlorendic anhydride, and maleic anhydride.
[0111] When a thermosetting agent is used, a curing catalyst may be used in combination. Examples of the curing catalyst include imidazole derivatives, guanamines, polyamines, organic acid salts thereof, epoxy adducts, triazine derivatives, tertiary amines, organic phosphines, phosphonium salts, quaternary ammonium salts, and the like.
[0112] The content of the thermosetting agent is not particularly limited, and can be, for example, 0.1% by mass or more and 10% by mass or less relative to the total mass of the ink.
[0113] It should be noted that when the ink contains a thermosetting agent, it is preferred that the polymerizable compound contain: a compound having an epoxy group, an oxetanyl group, a carboxyl group, etc. as a functional group that reacts with the thermosetting agent. On the other hand, when the polymerizable compound does not contain a functional group that reacts with the thermosetting agent, the polymerization of the polymerizable compound can be promoted by utilizing the heat dissipation reaction of the thermosetting agent.
[0114] Examples of surfactants include anionic surfactants such as dialkyl sulfosuccinates, alkylnaphthalene sulfonates, and fatty acid salts. Examples include polyoxyethylene alkyl ethers and polyoxyethylene alkyl allyl ethers. Examples include nonionic surfactants such as acetylene glycols and polyoxyethylene-polyoxypropylene block copolymers. Examples include cationic surfactants such as alkylamine salts and quaternary ammonium salts, and silicone-based and fluorine-based surfactants.
[0115] The content of the surfactant is not particularly limited, and can be, for example, 0.001% by mass or more and less than 1.0% by mass relative to the total mass of the ink.
[0116] The gelling agent is a compound that makes the ink in a gel state at room temperature (25°C) and in a sol state when heated (for example, 80°C). For example, the gelling agent is preferably a compound that dissolves in the liquid components (polymerizable compounds and organic solvents, etc.) contained in the ink at a temperature higher than the gelling temperature of the ink and crystallizes at a temperature below the gelling temperature of the ink. The so-called gelling temperature refers to the temperature at which the ink changes from a sol phase to a gel and the viscosity of the ink changes rapidly when the ink that has been solified or liquidized by heating is cooled. Specifically, the temperature at which the viscosity of the solified or liquidized ink rises rapidly when the viscosity is measured using a rheometer (for example, MCR300 manufactured by Anton Paar) while being cooled can be set as the gelling temperature of the ink.
[0117] Examples of gelling agents include ketone wax, ester wax, petroleum wax, plant wax, animal wax, mineral wax, solidified castor oil, modified wax, higher fatty acid, higher alcohol, hydroxystearic acid, fatty acid amide including N-substituted fatty acid amide and special fatty acid amide, higher amine, ester of sucrose fatty acid, synthetic wax, dibenzylidene sorbitol, dimer acid and dimer diol.
[0118] The content of the gelling agent is preferably 1.0 mass % to 10.0 mass % based on the total mass of the ink, more preferably 2.0 mass % to 7.5 mass %, and even more preferably 2.0 mass % to 3.5 mass %.
[0119] Examples of the polymerization inhibitor include N-oxyl-based polymerization inhibitors, phenol-based polymerization inhibitors, quinone-based polymerization inhibitors, amine-based polymerization inhibitors, and copper dithiocarbamate-based polymerization inhibitors. The polymerization inhibitor may be contained in the ink alone or in combination of two or more.
[0120] Examples of N-oxyl-based polymerization inhibitors include 4-hydroxy-2,2,6,6-tetramethylpiperidine-N-oxyl (TEMPO) and 4-hydroxy-2,2,6,6-tetramethyl-piperidine-N-oxyl. Examples include 4-oxo-2,2,6,6-tetramethyl-piperidine-N-oxyl and 4-methoxy-2,2,6,6-tetramethyl-piperidine-N-oxyl. Examples include 4-acetoxy-2,2,6,6-tetramethyl-piperidine-N-oxyl and the like. Examples of commercially available N-oxyl-based polymerization inhibitors include Irgas tab UV10 (manufactured by BASF ("Irgas tab" is a registered trademark of the company)).
[0121] Examples of phenolic polymerization inhibitors include 2,6-di-tert-butylphenol, 2,4-di-tert-butylphenol, and 2-tert-butyl 4,6-dimethylphenol. Examples include 2,6-di-tert-butyl-4-methylphenol and 2,4,6-tri-tert-butylphenol. Examples include 2,6-di-tert-butyl-p-cresol (butylated hydroxytoluene: BHT), 4-methoxyphenol, and 2-methoxy-4-methylphenol.
[0122] Examples of the quinone-based polymerization inhibitor include hydroquinone, methoxyhydroquinone, benzoquinone, 1,4-naphthoquinone, and p-tert-butylcatechol.
[0123] Examples of the amine-based polymerization inhibitor include alkylated diphenylamine, N,N′-diphenyl-p-phenylenediamine, and phenothiazine.
[0124] Examples of the copper dithiocarbamate-based polymerization inhibitor include copper dimethyl dithiocarbamate, copper diethyl dithiocarbamate, and copper dibutyl dithiocarbamate.
[0125] The content of the polymerization inhibitor is not particularly limited, and can be, for example, 0.01% by mass or more and 0.5% by mass or less relative to the total mass of the ink.
[0126] The ink may contain a solvent other than the polymerizable compound, such as water and an organic solvent.
[0127] Examples of organic solvents include aliphatic alcohols, aromatic alcohols, diols, triols, glycol ethers, poly(glycol) ethers, lactams, formamides, and acetamides. Examples include long-chain alcohols, ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, glycerol, dipropylene glycol, and ethylene glycol butyl ether. Examples include diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, diethylene glycol dibutyl ether, dipropylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, polyethylene glycol, and polypropylene glycol. Examples include methyl oleate, methyl caprylate, methyl caprate, methyl laurate, methyl myristate, methyl palmitate, methyl stearate, methyl oleate, and tallow fatty acid methyl ester. Examples include rice bran fatty acid methyl ester, rapeseed fatty acid methyl ester, soybean fatty acid methyl ester, n-butyl palmitate, and n-butyl stearate. Contains rapeseed fatty acid n-butyl ester, soybean fatty acid n-butyl ester, rice bran fatty acid isobutyl ester, rapeseed fatty acid isobutyl ester, palmitic acid octyl ester, oleic acid octyl ester, rapeseed fatty acid octyl ester, and vegetable fatty acid octyl ester. Contains isopropyl myristate and isopropyl palmitamide. Contains amines, ethers, carboxylic acids, esters, organic sulfides, organic sulfoxides, sulfones, alcohol derivatives, carbitol, butyl carbitol, cellosolves, ether derivatives, amino alcohols, and ketones.
[0128] It should be noted that silica particles are not easily wetted by water. Therefore, water easily causes silica particles to condense and easily hinders the adsorption of silica particles to inorganic particles. From the viewpoint of easily making silica particles adsorbed on inorganic particles and easily making settled inorganic particles redispersed, it is preferred that the ink is substantially free of water. In addition, from the viewpoint of suppressing the reduction of the durability of components such as inkjet heads or suppressing the reduction of the ejectability of ink, it is preferred that the ink is substantially free of water.
[0129] In addition, the silica particles treated by hydrophobization are excessively wetted by organic solvents. Therefore, organic solvents are strongly attached to the surroundings of silica particles, making silica particles difficult to approach inorganic particles, sometimes hindering the adsorption of silica to inorganic particles. From the viewpoint of making silica particles easily adsorbed on inorganic particles, easily making the inorganic particles of sedimentation redispersed, suppressing the reduction of the durability of components such as inkjet heads, suppressing the reduction of the ejectability of ink, preferably ink is substantially free of organic solvents.
[0130] In this specification, the term "ink substantially does not contain a certain component" means that the content of the component relative to the total mass of the ink is 5% by mass or less. From the above viewpoints, the content of water relative to the total mass of the ink is preferably 0% by mass or more and 1% by mass or less, more preferably 0% by mass or more and 0.1% by mass or less. In addition, the content of the organic solvent relative to the total mass of the ink is preferably 0% by mass or more and 1% by mass or less, more preferably 0% by mass or more and 0.1% by mass or less.
[0131] 1-4. Physical properties of ink
[0132] The viscosity of the ink is not particularly limited, but the viscosity at 25°C is preferably 5 mPa·s or more and 1000 mPa·s or less, and more preferably 20 mPa·s or more and 500 mPa·s or less. The ink is often stored and kept on standby at around 25°C. Moreover, the lower the viscosity at 25°C, the easier it is to redisperse the precipitated inorganic pigment. On the other hand, by appropriately increasing the viscosity at 25°C, the precipitation of the inorganic pigment can be suppressed.
[0133] The viscosity of the composition at 25° C. can be a value obtained using a rheometer at a shear rate of 1000 / sec. The rheometer can be a stress-controlled rheometer Physica MCR series manufactured by Anton Paar. The cone plate diameter can be 75 mm, and the cone angle can be 1.0°.
[0134] As for the ink, it is preferable to form an ink having a volume resistivity of 10 11 The surface resistivity of the cured film can be measured using HiResta UX (manufactured by Nitto Seiko Analytic Corporation, MCP-HT800).
[0135] 1-5. Preparation method of ink
[0136] The ink can be prepared by mixing the above-mentioned components. In this case, the components other than the inorganic particles may be mixed first, and the inorganic particles may be added to the obtained mixture later.
[0137] In addition, when the inorganic particles are dispersed by a dispersant, a dispersion liquid containing the inorganic particles, the dispersant and the liquid component can be prepared in advance, and the remaining components are added and mixed. At this time, in order to improve the solubility of the dispersant, etc., it is preferred to heat the inorganic particles and the dispersant, etc. and mix them to prepare the dispersion liquid.
[0138] When dispersing inorganic particles with a dispersant, silica particles may be added in advance for dispersion. From the viewpoint of allowing the silica particles to be wetted by the ink and to enter between the inorganic particles, it is preferred to add the silica particles in advance during dispersion.
[0139] 2. Method for forming a solidified product
[0140] The above-mentioned ink can be applied to a substrate by an inkjet method, cured, and used to form a cured product.
[0141] The application of the substrate may be performed by discharging ink from an inkjet head and causing the ink to fall onto the substrate.
[0142] As for the discharge method from the inkjet head, both the on-demand method and the continuous method are possible. The on-demand method inkjet head includes electro-mechanical conversion methods such as single-chamber type, dual-chamber type, supplier type, piston type, shared pattern type and shared wall type. It includes electro-thermal conversion methods such as thermal inkjet type and Bubble Jet ("Bubble Jet" is a registered trademark of Canon Inc.) type.
[0143] These inkjet heads or image forming devices having the inkjet heads may have a structure for circulating ink inside or outside the inkjet head. When the ink is discharged while circulating, if inorganic particles settle in the circulation flow path of the ink, the discharge property of the ink may be reduced. In contrast, the settled inorganic particles in the present embodiment have good redispersibility, so good discharge property can be maintained even when the ink is circulated.
[0144] The type of substrate is not particularly limited, for example, it can be paper, resin film, ABS resin plate, acrylic resin plate, aluminum plate, glass plate, polycarbonate plate, cloth, etc. It should be noted that the shape of the substrate is not particularly limited, except for plate-like, film-like, sheet-like, it can also be various three-dimensional shapes. In addition, in the space formed inside the substrate, the composition can be given by various methods.
[0145] As for the curing of the ink, it can be carried out by polymerizing and cross-linking the polymerizable compound through irradiation with active energy rays. Examples of active energy rays include electron beams, ultraviolet rays, α rays, γ rays, and X-rays. Among these, ultraviolet rays and electron beams are preferred. The above-mentioned ultraviolet rays are preferably light with a peak wavelength of more than 360nm and less than 410nm. In addition, it is preferred to irradiate the above-mentioned ultraviolet rays from an LED light source. As for LEDs, compared with previous light sources (such as metal halide lamps, etc.), the radiant heat is less, so if LEDs are used, the ink is difficult to dissolve when irradiated with active energy rays, and it is not easy to produce uneven gloss.
[0146] When ultraviolet rays are used as active energy rays, the amount of light per irradiation is preferably 500 mJ / cm 2 Above and 4000mJ / cm 2 Below. If 500mJ / cm 2 If the curing property of the polymerizable compound is 4000 mJ / cm 2 Hereinafter, discoloration of the cured product can be suppressed.
[0147] When forming a thick cured product, the application of ink and film formation can be repeated.
[0148] It is considered that the silica particles adsorbed on the surface of the inorganic particles are adsorbed or attached to the surface of the inorganic particles even in the interior of the solidified product. Therefore, in the solidified product formed in this embodiment, the surface of the inorganic particles is protected by the silica particles and has high abrasion resistance.
[0149] After the cured product is produced in this way, a protective film can be formed by covering the cured product with a varnish, a laminate film, an ink, or the like, or the cured product can be processed into a desired shape.
[0150] Example
[0151] Hereinafter, the present invention will be specifically described with reference to Examples, but the scope of the present invention is not limited to the description of the Examples.
[0152] [Experiment 1]
[0153] 1. Preparation of Materials
[0154] Using the following materials, an inkjet ink was prepared.
[0155] 1-1. Polymerizable compounds
[0156] Monomer 1: Neopentyl glycol diglycidyl ether (difunctional, non-aromatic)
[0157] Monomer 2: 1,6-Hexanediol diglycidyl ether (2-functional, non-aromatic)
[0158] Monomer 3: triethylene glycol divinyl ether (difunctional, non-aromatic)
[0159] Monomer 4: 3,3'-(oxybismethylene)bis(3-ethyloxetane) (2-functional, non-aromatic)
[0160] Acrylate 1: Dipropylene glycol diacrylate (2-functional, non-aromatic)
[0161] Acrylate 2: Polyethylene glycol (200) diacrylate (2-functional, non-aromatic)
[0162] Acrylate 3: 1,6-Hexanediol diacrylate (2-functional, non-aromatic)
[0163] Acrylate 4: Isobornyl acrylate (monofunctional, non-aromatic)
[0164] Acrylate 5: Cyclic trimethylolpropane formal acrylate (monofunctional, non-aromatic)
[0165] Acrylate 6: Benzyl acrylate (monofunctional, aromatic)
[0166] Acrylate 7: Phenol 4EO acrylate (monofunctional, aromatic)
[0167] Acrylate 8: 2-phenoxyethyl acrylate (monofunctional, aromatic)
[0168] Acrylate 9: Glycidyl ether group-containing epoxy acrylate oligomer (manufactured by Shin-Nakamura Chemical Co., Ltd., NK Oligo EA-1010N) (multifunctional, aromatic)
[0169] 1-2. Inorganic particles
[0170] Inorganic particles 1: zinc oxide (Candy Zinc 1000 manufactured by Sakai Chemical Industry Co., Ltd. ("Candy Zinz" is a registered trademark of the company))
[0171] Inorganic particles 2: barium sulfate (manufactured by Sakai Chemical Industry Co., Ltd., H-LFM)
[0172] Inorganic particles 3: Pearlescent pigment (manufactured by Melco Corporation, Iriodin 111 104259 ("Iriodin" is a registered trademark of the company))
[0173] Inorganic particles 4: Luminous pigment (manufactured by Nemoto Chemical Co., Ltd., Luminova G-300F ("Luminova" is a registered trademark of the company)
[0174] Inorganic particles 5: Luminous pigment (manufactured by Nemoto Chemical Co., Ltd., Luminova G-300FF)
[0175] 1-3. Silica particles
[0176] Silica 1: QSG-170 (average particle size: 170 nm) manufactured by Shin-Etsu Chemical Co., Ltd. Hydrophobicity: 67%
[0177] Silica 2: QSG-130 (average particle size: 130 nm) manufactured by Shin-Etsu Chemical Co., Ltd. Hydrophobicity: 67%
[0178] Silica 3: QSG-30 (average particle size: 30 nm) manufactured by Shin-Etsu Chemical Co., Ltd. Hydrophobicity: 67%
[0179] Silica 4: QSG-10 (average particle size: 10 nm) manufactured by Shin-Etsu Chemical Co., Ltd. Hydrophobicity: 67%
[0180] Silica 5: Rheorosil MT-10 (average particle size: 15 nm) manufactured by Tokuyama Co., Ltd. ("Rheorosil" is a registered trademark of the company)
[0181] Silica 6: manufactured by Tokuta Co., Ltd., Rikoli DM-10 (average particle size: 15 nm)
[0182] Silica 7: Manufactured by Tokuta Co., Ltd., Rikoli HM-20L (average particle size: 12 nm)
[0183] Silica 8: manufactured by Tokuyama Co., Ltd., Lerosil ZD-30ST (average particle size: 7 nm)
[0184] Silica 9: Silfil NHM-3N manufactured by Tokuyama Co., Ltd. (average particle size: 150 nm, “Silfil” is a registered trademark of the company)
[0185] Silica 10: Sansil SP-01MS (average particle size: 100 nm), manufactured by Tokuyama Co., Ltd. (“Sansil” is a registered trademark of the company)
[0186] Silica 11: Made by Tokuta Co., Ltd., Sunshine SP-01P (average particle size: 100nm)
[0187] Silica 12: Manufactured by Tokuta Co., Ltd., Sunshine SP-04MS (average particle size: 400nm)
[0188] Silica 13: manufactured by Tokuta Co., Ltd., Sunshine SP-03P (average particle size: 300nm)
[0189] Silica 14: Manufactured by Tokuta Co., Ltd., Sunshine SP-10M (average particle size: 1000nm)
[0190] Silica 15: Manufactured by Tokuta Co., Ltd., Sunshine SP-10P (average particle size: 1000nm)
[0191] Silica 16: Manufactured by Tokuta Co., Ltd., Rikoli QS-09 (average particle size: 20nm)
[0192] Silica 17: Silfi NSS-3N manufactured by Tokuyama Co., Ltd. (average particle size: 150 nm)
[0193] Silica 18: manufactured by Tokuyama Co., Ltd., Sansil SS-03 (average particle size: 300 nm)
[0194] Silica 19: SC2300-SVJ manufactured by ADOMATICS CO., LTD. (average particle size: 500 nm)
[0195] Silica 20: SC2500-SMJ manufactured by ADOMATICS CO., LTD. (average particle size: 500 nm)
[0196] Silica 21: PGM-AC-4130Y manufactured by Nissan Chemical Co., Ltd. (average particle size: 45 nm)
[0197] Silica 22: manufactured by Nissan Chemical Co., Ltd., MEK-AC-4130Y (average particle size: 45 nm)
[0198] It should be noted that silica 1 to silica 15 are silica particles that have been hydrophobized and do not contain polymerizable groups. Silica 16 to silica 18 are silica particles that are hydrophilic and do not contain polymerizable groups because they have not been hydrophobized. Silica 19 is a silica particle that has been hydrophobized and contains a vinyl group as a polymerizable group. Silica 20 is a silica particle that has been hydrophobized and contains a methacryloyl group as a polymerizable group. Silica 21 is a silica particle that has been hydrophobized and contains an acryloyl group as a polymerizable group. Silica 22 is a silica particle that has been hydrophobized and contains an acryloyl group as a polymerizable group.
[0199] 1-4. Photopolymerization initiator
[0200] Initiator 1: Omnirad MBF manufactured by IGM RESINS BV
[0201] Initiator 2: Omnirad 754 manufactured by IGM RESINS BV
[0202] Initiator 3: Omnirad 819 manufactured by IGM RESINS BV
[0203] 1-5. Thermal curing agent
[0204] Thermal curing agent 1: dicyandiamide
[0205] Thermal curing agent 2: Blocked isocyanate BI7982 manufactured by LANXESS
[0206] Thermal curing agent 3: 2-ethyl-4-methylimidazole
[0207] 1-6. Organic solvents
[0208] Organic solvent 1: methyl oleate
[0209] Organic solvent 2: methyl ethyl ketone
[0210] 1-7. Other ingredients
[0211] Inhibitor: BASF, Irgastab UV-10
[0212] 2. Preparation of Inkjet Ink
[0213] 2-1. Preparation of dispersion
[0214] 20 parts by mass of inorganic particles 1, 80 parts by mass of monomer 1 and 50 parts by mass of zirconium oxide beads having an average particle size of 0.3 mm were placed in a polypropylene container and dispersed for 30 minutes using a paint shaker to remove the zirconium oxide beads, thereby preparing dispersion 1A-1.
[0215] 20 parts by mass of inorganic particles 1, 80 parts by mass of monomer 2, and 50 parts by mass of zirconium oxide beads having an average particle size of 0.3 mm were placed in a polypropylene container and dispersed for 30 minutes using a paint shaker to remove the zirconium oxide beads, thereby preparing dispersion 1A-2.
[0216] 20 parts by mass of inorganic particles 1, 80 parts by mass of acrylate 1 and 50 parts by mass of zirconium oxide beads having an average particle size of 0.3 mm were placed in a polypropylene container and dispersed for 30 minutes using a paint shaker to remove the zirconium oxide beads, thereby preparing dispersion 1A-3.
[0217] Dispersion liquid 1B was prepared in the same manner as in the preparation of dispersion liquid 1A-3 except that the dispersion time was changed to 2 hours.
[0218] Dispersions 1C to 1F were prepared in the same manner as in the preparation of dispersion 1A-3 except that the inorganic particles were changed to inorganic particles 2 to inorganic particles 5 .
[0219] Dispersion liquid 1G was prepared in the same manner as in the preparation of dispersion liquid 1F except that the dispersion time was changed to 8 hours.
[0220] Dispersion liquid 1H was prepared in the same manner as in the preparation of dispersion liquid 1F except that the dispersion time was changed to 10 hours.
[0221] Dispersion liquid 1I was prepared in the same manner as in the preparation of dispersion liquid 1F except that the dispersion time was changed to 16 hours.
[0222] Then, the median diameter of the inorganic particles in the dispersion was measured using a particle size distribution analyzer using the Stokes sedimentation method (LUMiSizer manufactured by LUM Japan Co., Ltd.).
[0223] 2-2. Preparation of ink
[0224] A polymerizable compound, a dispersion, silica particles, a photopolymerization initiator, a thermosetting agent, an organic solvent, water, and a polymerization inhibitor were mixed in the ratios listed in Tables 1 to 10, and filtered using a 30 μm polypropylene Buchner filter (manufactured by RokiTechno Co., Ltd.) to obtain Ink 1 to Ink 65. The values listed in parentheses in the columns of "inorganic particles" and "silica particles" in Tables 1 to 10 are the median diameter and average particle size of each particle in the dispersion.
[0225]
Table 1
[0226]
[0227]
Table 2
[0228]
[0229]
Table 3
[0230]
[0231]
Table 4
[0232]
[0233]
Table 5
[0234]
[0235]
Table 6
[0236]
[0237]
Table 7
[0238]
[0239]
Table 8
[0240]
[0241]
Table 9
[0242]
[0243]
Table 10
[0244]
[0245] 3. Evaluation
[0246] The following evaluations were performed on Ink 1 to Ink 65 prepared above.
[0247] 3-1. Sedimentation recovery
[0248] 10 g of a sample was placed in a 20 mL glass sample tube and allowed to stand at 25° C. for 3 days to allow solids to accumulate at the bottom of the sample tube. The accumulation was vigorously shaken up and down by hand, and the number of shakes required to loosen the accumulation was measured.
[0249] A is used 1 to 10 times, and the deposits are almost completely peeled off from the bottom of the sample tube.
[0250] B was used 11 to 30 times, and the deposits were almost completely peeled off from the bottom of the sample tube.
[0251] C Up to the 31st time, the deposits were not peeled off from the bottom of the sample tube.
[0252] 3-2. Injection bending
[0253] The ink was filled in an independently driven inkjet head (360 npi, discharge volume 27 pL, 1024 nozzles) manufactured by Konica Minolta, and a continuous discharge test was carried out for 10 minutes using a strobe-synchronized droplet observation device. Then, the ejection deflection was evaluated according to the following criteria.
[0254] (standard)
[0255] A: All 256 nozzles among the 256 nozzles evaluated discharged normally.
[0256] B: Among the 256 nozzles evaluated, one or more and less than five nozzles were observed to have injection bending nozzles.
[0257] C: Among the 256 nozzles evaluated, 5 or more nozzles were observed to have jet bending.
[0258] 3-3. Durability of components
[0259] A maintenance cloth (Zaviner CK: manufactured by KB Celeron Co., Ltd.) to which each ink was attached was placed against the nozzle surface of KM1024iLHE manufactured by Konica Minolta Inc. and rubbed 100 times, and then the surface of the nozzle surface was observed.
[0260] A Almost no damage was found
[0261] B Slightly damaged
[0262] C. Found major damage
[0263] 3-4. Yellowing
[0264] Ink 1 to Ink 65 were applied to a substrate of a 160 mm×160 mm ABS plate with a thickness of 2 mm. A UV LED curing lamp (FireJet FJ100 manufactured by Phoseon) was used with an irradiation wavelength of 365 nm and an illuminance of 2 W / cm 2 , Light intensity 2000mJ / cm 2 The obtained cured products were cured by ultraviolet light to produce cured products with a film thickness of 300 micrometers. The appearance of the cured products after standing in a 60°C thermostatic bath for 5 days was observed as follows.
[0265] A Compared with before the test, almost no change was found after the test
[0266] B. Slight color change was found in the cured film compared to before the test.
[0267] 3-5. Weather resistance
[0268] Ink 1 to Ink 65 were applied to a substrate of a 160 mm×160 mm ABS plate with a thickness of 2 mm. A UV LED curing lamp (FireJet FJ100 manufactured by Phoseon) was used with an irradiation wavelength of 365 nm and an illuminance of 2 W / cm 2 , Light intensity 2000mJ / cm 2 The cured products were cured by ultraviolet rays to produce 300 micron thick cured products. Each cured product was subjected to a weathering test in accordance with JIS B 7753:2007. Specifically, a sunlight carbon arc lamp accelerated weathering tester (manufactured by Suga Test Instrument Co., Ltd., Sunshine Weather Meter S80) was used. For the substrate with each cured product, the irradiance in the wavelength range of 300 nm to 700 nm was continuously set to 255 W / m 2 102 minutes of light exposure and 18 minutes of water spray.
[0269] ○ There was almost no color change in the cured film after the test compared to before the test.
[0270] △Compared with before the test, the color of the cured film was slightly changed after the test.
[0271] The evaluation results of each ink are shown in Tables 11 to 20. The values recorded in the column "Silica Diameter / Inorganic Particle Diameter" in Tables 11 to 20 are the ratios of the average particle diameter of the silica particles to the median diameter of the inorganic particles used in each ink. "A" indicates 1 / 20 or less, "B" indicates greater than 1 / 20 and less than 1 / 1, and "C" indicates 1 / 1 or more.
[0272]
Table 11
[0273]
[0274]
Table 12
[0275]
[0276]
Table 13
[0277]
[0278]
Table 14
[0279]
[0280]
Table 15
[0281]
[0282]
Table 16
[0283]
[0284]
Table 17
[0285]
[0286]
Table 18
[0287]
[0288]
Table 19
[0289]
[0290]
Table 20
[0291]
[0292] As can be seen from the results of Tables 1 to 20, an ink having a polymerizable compound, inorganic particles, and hydrophobized silica particles without a polymerizable group is prepared. The average particle size of the silica particles is smaller than the median diameter of the inorganic particles, and the mass-based content of the silica particles is less than the mass-based content of the inorganic particles. The active energy ray-curable inkjet ink has excellent redispersibility of the precipitated inorganic particles. In addition, the above-mentioned inkjet ink contains an inorganic pigment, but it is not easy to reduce the durability of components such as inkjet heads and reduce the ejectability of ink.
[0293] [Experiment 2]
[0294] In order to confirm the D 50 and D 90 The following experiment was conducted to investigate the difference in sedimentation recovery. It should be noted that in the following description, the contents common to Experiment 1 are omitted, and the differences from Experiment 1 are described. In addition, the materials used and their abbreviations are the same as those in Experiment 1, and the description is omitted.
[0295] 1. Preparation of Inkjet Ink
[0296] 1-1. Preparation of dispersion
[0297] 50 parts by mass of inorganic particles 4 and 50 parts by mass of acrylate 1 were placed in a polypropylene container together with 100 parts by mass of zirconium oxide beads having an average particle size of 0.3 mm, and dispersed for 30 minutes using a paint shaker to remove the zirconium oxide beads, thereby preparing dispersion 2A.
[0298] Dispersion liquid 2B was prepared in the same manner as dispersion liquid 2A except that the inorganic particles were changed to inorganic particles 5 .
[0299] Dispersion liquid 2C was prepared in the same manner as in the preparation of dispersion liquid 2B except that the dispersion time was changed to 8 hours.
[0300] 1-2. Preparation of ink
[0301] The polymerizable compound, dispersion, silica particles, photopolymerization initiator, thermosetting agent, organic solvent, water and polymerization inhibitor were mixed in the ratios listed in Table 21, and filtered through a 30 μm polypropylene Buchner filter (manufactured by RokiTechno Co., Ltd.) to obtain Ink 66 to Ink 73. The values listed in parentheses in the columns of "inorganic particles" and "silica particles" in Table 21 are the median diameter and average particle size of each particle in the dispersion.
[0302] Ink 66 to Ink 73 were diluted with dipropylene glycol diacrylate, and the D of the inorganic particles contained in each ink was measured using a particle size distribution analyzer (LUMiSizer, manufactured by LUM Japan Co., Ltd.).50 and D 90 . Determination of D 50 , D 90 and D 50 / D 90 Also shown in Table 21.
[0303]
Table 21
[0304]
[0305] Ink 66 to Ink 73 were evaluated in the same manner as in Experiment 1. Table 22 shows the results.
[0306]
Table 22
[0307]
[0308] From the results in Table 21 and Table 22, it can be seen that the D 90 The larger the D of the inorganic particles, the higher the recovery of the inorganic particles from sedimentation. 50 / D 90 The smaller it is, the higher the weather resistance of the cured product.
[0309] Although the embodiments of the present invention have been described and illustrated in detail, it should be clearly understood that this is for illustration and example only and not for limitation, and the scope of the present invention is to be interpreted by the appended claims.
Claims
1. An active energy ray-curable inkjet ink comprising a polymerizable compound, inorganic particles, and silica particles, The silica particles are hydrophobized and have no polymerizable groups. The average particle size of the silica particles is smaller than the median diameter of the inorganic particles. The content of the silica particles based on mass is smaller than the content of the inorganic particles based on mass.
2. The inkjet ink according to claim 1, wherein The polymerizable compound includes a (meth)acrylate.
3. The inkjet ink according to claim 2, wherein: The (meth)acrylate includes a monofunctional polymerizable compound having an aromatic ring.
4. The inkjet ink according to claim 1 or 2, which is substantially free of water and substantially free of organic solvents.
5. The inkjet ink according to claim 1 or 2, wherein: The average particle diameter of the silica particles is 1 / 20 or less of the median diameter of the inorganic particles.
6. The inkjet ink according to claim 1 or 2, wherein: The content of the silica particles is 0.01% by mass or more and 5% by mass or less relative to the total mass of the inkjet ink.
7. The inkjet ink according to claim 1 or 2, wherein: The average particle size of the inorganic particles is 0.5 μm or more and 5 μm or less.
8. The inkjet ink according to claim 1 or 2, wherein: The D of the inorganic particles 50 / D 90 It is 0.1 or more and 0.9 or less.
9. The inkjet ink according to claim 1 or 2, wherein: The inorganic particles are light-storing pigments.
10. The inkjet ink according to claim 1 or 2, comprising a thermal curing agent.
11. A method for forming a solidified product, comprising: The step of applying the inkjet ink according to any one of claims 1 to 10 to a substrate; and The step of irradiating the applied inkjet ink with active energy rays.
12. The method for forming a cured product according to claim 11, wherein: The step of applying the ink to the substrate is performed while the inkjet ink is circulated. 13 . A cured product formed using the inkjet ink according to claim 1 .
Citation Information
Patent Citations
Inkjet recording ink composition and recorded matter
JP2013181055A
Active energy ray-curable composition, active energy ray-curable inkjet ink and inkjet recording device
JP2019157062A